PENGAMBILAN KEPUTUSAN UNTUK MENIKAH BEDA ETNIS: STUDI FENOMENOLOGIS PADA PEREMPUAN JAWA - Tuapattinaya, Yolanda Imelda Fransisca; Hartati, Sri (Jurnal Psikologi, 2014)
Abstract It is uneasy for Javanese women to make a decision to marry a non-Javanese man. Previous experiences withinter-ethnicities socialization play important roles to influence one’s decision to undergo an inter-ethnicitiesmarriage. Decision-making process is defined as a selection process of many available alternatives, includingcognitive, motive, and attitude aspects. This study aims to describe the decision making process of the Javanesewomen t o ma r r y n o n -Javanese men. Three adult women (within age range 20-40 years old), who were Javanese,and married with a non-Javanese man (Bataknese or Papuan) participated in this study. Observation and depthinterview were used to collect qualitative data. The findings show that having similarities in age and religiousbeliefs (or religion) were the main consideration for these Javanese women to marry their non-Javanese husband.Two Javanese women encountered parents’ disagreement with their decisions to marry a non-Javanese man;parents encouraged them to marry a Javanese man. Another one woman could choose freely her non-Javaneseman to marry with. The results also indicated that their decision making to marry followed these five steps:appraising the challenge, surveying alternatives, weighing of alternatives, deliberating about commitment, andsurviving from negative feedback. Love and intimacy were two internal factors they considered before makingdecision to marry a non-Javanese man.